2021
DOI: 10.1088/1757-899x/1036/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Groundwater in Omu-Aran, Nigeria

Abstract: Pollution of groundwater by bathroom, laundry and kitchen effluent has been documented to have non-desirable health and environmental effects. There is little information about the quality of groundwater and associated health effects in Omu-Aran. The present research therefore meets the need to investigate the levels of heavy metals, the pollution effects, and the long term human health risk effect on local inhabitants in Omu-Aran. Thirty water samples were collected from five hand dug wells (HWs) in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Excess iron in the human body will interfere with health such as heart attacks, and disorders of blood vessels, and dangerously can cause liver cancer. This happens because iron accumulates, especially in the filtering organs that can attack the physiological functions of the human body [16]. Kapuk Muara is also an area experiencing a decline in water quality with high iron concentrations occurring in 2018 and 2020.…”
Section: Iron Contaminationmentioning
confidence: 99%
“…Excess iron in the human body will interfere with health such as heart attacks, and disorders of blood vessels, and dangerously can cause liver cancer. This happens because iron accumulates, especially in the filtering organs that can attack the physiological functions of the human body [16]. Kapuk Muara is also an area experiencing a decline in water quality with high iron concentrations occurring in 2018 and 2020.…”
Section: Iron Contaminationmentioning
confidence: 99%
“…The observations triggered suggestions for comprehensive sources' monitoring and appropriate treatment of the sampled water to help in the realisation of good health and well-being (SDG 3) and its associate (SDG 11) considered in this study. Five hand-dug wells for 30 water samples were compared with WHO limits and health risk assessment of ingestion and dermal in Omu-Aran, Kwara State, Nigeria, by Elemile et al (2021). The results showed that 5 over 7 analysed metals exceeded the WHO limits, while ingestion but dermal index indicated noncarcinogenic effects for all the samples.…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic activities have been found to influence groundwater quality (Moyo, 2013;Elemile et al 2019a,b) and majority of the microbial contaminants come from fecal sources of animals and humans (Takal and Quaye-ballard, 2018). Pathogenic microorganisms should not be found in water resources as disease outbreaks, including cholera and dysentery, are often the result of such contamination, according to the World Health Organization (WHO) According to Elemile et al (2021), health challenges are the resultant effect of water pollution. Therefore, providing safe potable water, adequate sanitation and hygiene, are essential in protecting health, and directly contribute to achieving good health and well-being (United Nations 2018).…”
Section: Introductionmentioning
confidence: 99%